Diversity and Distribution of Conidae from the TamilNadu Coast of India (Mollusca: Caenogastropoda: Conidae) - Franklin, J. Benjamin; Subramanian, K. A.; Fernando, S. Antony; Krishnan, K. S. (Zootaxa, 2009)
A survey of the marine gastropod genus Conus Linnaeus was conducted along the TamilNadu Coast of India to explore the regional geographic distribution and diversity. The 60 species observed increased the number of Indian Conidae from 77 to 81. Conus imperialis Linné, C. mitratus Hwass in Bruguière, C. striolatus Kiener and C. violaceus Gmelin are newly recorded from the study area. Conus amadis Gmelin was the most widely distributed species. The highest diversity (48 species) occurred in the Gulf of Mannar, followed by 22 species from northern, six from southern, and five from the Palk Bay regions. We suggest that the rich diversity recorded in the Gulf of Mannar reflects the physical conditions, microhabitats and required resources such as food and shelter that favour the occurrence of the large number of Conus species.